Factors influencing job satisfaction of female school principals in the Eastern province of Saudi Arabia - Abubakar, Jamila Muazu (2015)
The widely held premise that satisfied principals are likely to have better retention rates and serve as the best advertisement for attracting future leaders has generated the need to consistently explore principals’ job satisfaction. With the recent leadership crisis of principals’ attrition and decreasing interest by teachers in taking up principalship positions due to their perception that principals are overworked, overstressed and underpaid, the need to explore principals’ job satisfaction and factors that influences job satisfaction for intervention purposes became ever more necessary. Moreover, a number of researchers continue to report that little attention has been given to job satisfaction of school principals despite its importance in understanding employees’ well-being, withdrawal, commitment, productivity, performance and job attitudes. The general objective of this study is to find out factors that influence female principals’ job satisfaction in the Eastern province of Saudi Arabia. While the specific objectives are to determine the level of job satisfaction, work-family conflict and family-work conflict among female principals in the Eastern province of Saudi Arabia; to compare the difference in job satisfaction based on age groups, experience in principalship, school size and school type; to determine the relationship between, work-family conflict, family-work conflict,age, experience in principalship, school size, and school type with job satisfaction; and to examine the predictive ability of work-family conflict,family-work conflict, age, experience in principalship, school size and school type on job satisfaction. The study used descriptive survey research design aligned with quantitative approach. The study found female principals as satisfied with their jobs based on the Mean score of 42.56 and standard deviation of 12.10. For the level of work – family conflict, descriptive analysis revealed moderate level of W-FC (M = 3.18, SD =1.03). Descriptive analysis also indicated moderate level of F-WC among respondents (M = 2.48, SD = 0.84). An independent-sample t-test revealed no significant difference in job satisfaction between 36 – 45 years age group (M= 41.84, SD = 10.93) and 46 years and above age group (M= 43.58, SD= 13.62), t (158) = -.895, p = .372. Similarly, the ANOVA analysis also indicated no significant difference in job satisfaction with regards to experience in principalship, F (2, 157) = .741, p = .479, school size, F(2, 157) = 1.845, p = .161 and school type, F(2,157) = .47, p = .954. Pearson correlation analysis revealed that there is a significant negative and medium relationship between work-family conflict and job satisfaction (r = -.446, p < .01) and between family-work conflict and job satisfaction (r = -.396, p <.01). The Pearson correlation analysis revealed no relationship between age and job satisfaction (r = 0.07, p <.05);experience in principalship and job satisfaction (r = 0.03, p <.05) and school type and job satisfaction (elementary school) (r = 0.01, p <.05); (high school) (r= 0.006, p <.05). However, the analysis revealed a significant low negative relationship between school size and job satisfaction (r = 0.18, p <.05). Multiple linear regression revealed work-family conflict as a significant predictor of job satisfaction (β = -.301, t = -3.074, p = .003). Family – work conflict was also revealed by the regression analysis to significantly contribute to job satisfaction (β = -.204, t = -2.109, p = .037). However, the regression analysis revealed all the demographic variables with the exception of school size as not significant predictors of job satisfaction, age (β = .001, t = .007, p = .995); experience in principalship (β = -.058, t = -.784, p = .434); school size (β = -.149, t = -2.041, p = .043) and school type: elementary (β = .055, t = .681, p = .497) and high school (β = .010, t = .128, p = .898). Although the study found principals as satisfied with their jobs, this should not be taken for granted. It is important for policy makers, superintendents and all those in charge of female principals in Saudi Arabia to put forth effort to either maintain this satisfaction or increase it to a higher level. Despite the moderate level of W-FC and F-WC among principals, there is need for family-friendly human resource management practices and related policies. This include employer assistance with dependent care, leaves to accommodate family needs, and counseling on family problems. Work-family conflict and family-work conflict should be considered in all intervention programs relating to female principals’ job satisfaction. These two variables have been found as the best predictors of female principal’s job satisfaction in the Eastern province of Saudi Arabia.